OPTIMALISASI PENGELOLAAN SISTEM APLIKASI INFORMASI DI LINGKUNGAN SKPA PROVINSI ACEH - Teuku Muhammad Mirza Keumala Keumala (Jurnal Pengabdian Pemersatu Bangsa, 2025)
Optimizing the management of information system applications is a crucial aspect in improving government performance and public service quality. This community service program aims to enhance human resource capacity and optimize the utilization of information system applications within the Aceh Provincial Government Work Units (SKPA). The implementation method consists of several stages, including needs assessment, system development and implementation using the Agile approach, socialization and training, as well as monitoring, evaluation, and assistance. The results indicate significant improvements in system quality, information quality, and service quality. The level of system adoption increased, with user satisfaction exceeding 85%. In addition, operational efficiency improved, as evidenced by a reduction in task completion time by up to 40%. The program also enhanced the technical competencies of human resources in managing information systems. Overall, this initiative provides a meaningful contribution to digital transformation within SKPA and has the potential to be replicated in other government institutions